Character, Discipline, Law: Courts Martial in World War I. Issue 3 (2nd July 2020) - Finnane, Mark; Smaal, Yorick
Abstract : Courts martial were as ubiquitous in the experience of World War I as criminal courts in civil life, yet they remain largely neglected in the Australian war historiography. Their remarkable evidentiary record, transmitted from the field of battle into the custody of the Attorney-General, has been used to highlight wartime dimensions of individual character and collective discipline. In this article, we review the uses of the courts martial in those respects. We note the significance of Australian exceptionalism in this military domain, and consider the potential of an approach that treats the court martial as a legal event.